17. EFFECTIVENESS OF A LIPID-RICH DIET FOR PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE EXACERBATION ON MECHANICAL VENTILATION AT MILITARY HOSPITAL 175 FROM 2021 TO 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the effectiveness of a lipid-rich diet for patients with chronic obstructive pulmonary disease exacerbations on mechanical ventilation at Military Hospital 175 from 2021 to 2023.Subjects and methods: The study was conducted using a comparative, controlled intervention study. The intervention group used soup to ensure that the patients were nourished. Conducted on 118 patients with a confirmed diagnosis of COPD exacerbation on mechanical ventilation at the Intensive Care Department, Military Hospital 175 from December 2021 to November 2023. Evaluate the effectiveness of nutritional status and biochemical index after intervention.Results: Weight in the soup and ensure groups increased more than the control group, and the SGA level A index before intervention increased after intervention. The protein index in the normal range increased in the intervention group and decreased in the control group. The changes were statistically significant (p0.05).Conclusion: Using a lipid-rich diet for patients with acute exacerbations of chronic obstructive pulmonary disease on mechanical ventilation has shown to be effective in improving nutritional status in patients.
Keywords: ventilation; Lipid-rich diet, COPD, mechanical ventilation.